2021
DOI: 10.3390/su13115938
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Educational Sustainability. Initial Perceptions of the University Community of the University of Cádiz

Abstract: This research analyses the impact of COVID-19 on the Spanish university system during the period of home lockdown put in place by the government of Spain between 15 March and 21 June 2020. This period did not involve a change to online teaching. Instead, it involved emergency remote teaching, wherein the content of face-to-face teaching was taught through non-classroom training using media, devices and tools available at that time. The main objective of the paper is related to the perceptions of students and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…In particular, rather than considering the educational effect, the class is conducted using a device that was available at the time. An early case of ERT operation is shown in a study conducted at a Spanish university from March to June, 2020, during the early stages of the outbreak [4]. This ERT was not unique to Spain but a phenomenon common to most countries [28,35,36].…”
Section: Covid-19 and Higher Eduction In The Worldmentioning
confidence: 97%
See 1 more Smart Citation
“…In particular, rather than considering the educational effect, the class is conducted using a device that was available at the time. An early case of ERT operation is shown in a study conducted at a Spanish university from March to June, 2020, during the early stages of the outbreak [4]. This ERT was not unique to Spain but a phenomenon common to most countries [28,35,36].…”
Section: Covid-19 and Higher Eduction In The Worldmentioning
confidence: 97%
“…Although these studies have been conducted in a wide variety of fields, studies on online and distance education and the health and psychological status of students and professors have been dominant. That is, in a situation where faceto-face classes had to be switched to online because of the sudden outbreak of COVID-19, the discussion on the implementation of effective online education was dominant [4][5][6][7][8][9][10][11][12]. Other than online education, numerous studies on university life and the health and psychological status of students and professors have been dominant [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Most universities replaced face-to-face learning with online learning since March 2020, and chose blended learning indefinitely (Chamberlain et al, 2020 ) after a smooth transition to normal offline education. Some other studies in different fields across the world also rate blended learning higher compared to face-to-face traditional learning or fully online learning (Amir et al, 2020 ; AlQhtani et al, 2021 ; Amro, 2022 ), but results in Spain (Alonso-García et al, 2021 ) and Philippines (Baloran, 2020 ) show a preference for face-to-face learning rather than online-blended learning. Besides the technological support and teacher inexperience of this remote teaching mode, teacher virtual presence and learner engagement are important factors that affect the learning process (Christopher et al, 2020 ; Matthews et al, 2021 ).…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, researches show that the willingness of students in choosing online learning is low and most students are not skilled at online learning in China (Bao, 2020 ; Zhang et al, 2020 ). The downside of long-term distancing and online isolation may directly impact learner engagement and effectiveness in general (Carlson, 2020 ), as evidenced in the UK (Walters et al, 2021 ), Australia (Abdel Latif, 2022 ), Qatar (Abouhashem et al, 2021 ), Malaysia (Al-Kumaim et al, 2021 ), South Korea (Almusharraf and Bailey, 2021 ), Spain (Alonso-García et al, 2021 ), Saudi Arabia (Alqahtani et al, 2021 ), India (Basri et al, 2022 ), and so on. But online language learning during the no-direct contact period was not an option, but a necessity (Gacs et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Against the background of this global situation, some authors, through their studies, found that experienced trainers in the field of PES handled this problem much better, managing to maintain a close link between trainers and students or athletes [11], whereas other authors noticed that training at home was rather difficult: either the location was unsuitable for exercise, or the athletes had difficulty trying to set up an internet connection for technical or financial reasons [12]. Some studies have shown that PES teachers/coaches need to develop and master IT, focusing on interaction and play so that students and athletes feel more motivated to actively participate in online training sessions [13], while studies conducted in academia have highlighted issues of interest such as teachers' views on online teaching methods and the availability of digital tools [14]. Other studies have drawn attention to the need for the creation of a relationship of trust and empathy between PES trainers and students and athletes so that the training process has good results under online conditions employing specific technology [15].…”
Section: Introductionmentioning
confidence: 99%